2019
DOI: 10.1055/s-0039-1692130
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy after Endometriosis: Maternal and Neonatal Outcomes according to the Location of the Disease

Abstract: Objective To systematically evaluate pregnancy and labor course, obstetrical complications, and maternal and neonatal outcomes in women with endometriosis, stratifying according to the specific location of the disease. Study Design We retrospectively analyzed our prospectively maintained obstetrical database from January 2011 to August 2014 to identify all women with a previous histological diagnosis of endometriosis who delivered at our institution (cases). We divided the cases according to the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
49
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(58 citation statements)
references
References 27 publications
(39 reference statements)
1
49
0
5
Order By: Relevance
“…A total of 11 cohort studies investigated hypertensive disorders in pregnancy overall [25,30,34,38,44,45,49,51,53,59,60]. Five were eligible for the main meta-analysis [30,34,38,51,53], without statistically significant difference between exposed and non-exposed to endometriosis ( Figure 2).…”
Section: Hypertensive Disorder In Pregnancy Overallmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 11 cohort studies investigated hypertensive disorders in pregnancy overall [25,30,34,38,44,45,49,51,53,59,60]. Five were eligible for the main meta-analysis [30,34,38,51,53], without statistically significant difference between exposed and non-exposed to endometriosis ( Figure 2).…”
Section: Hypertensive Disorder In Pregnancy Overallmentioning
confidence: 99%
“…A total of 13 cohorts were found on endometriosis and gestational age at birth. Seven studies found women with endometriosis to have a shorter duration of pregnancy compared to women without endometriosis [31,[39][40][41]43,55,60]. Two of these received a NOS score ≥7 [39,40].…”
Section: Gestational Age At Birthmentioning
confidence: 99%
See 2 more Smart Citations
“…6,7,15,16,21,28−41 The eligible studies were published between 2010 and 2020, all of which were retrospective studies, and none was a randomized controlled study; all studies were comparator studies. 6,7,15,16,21,28−41 Nearly a third of the studies were from Europe (n=8 [42.1%]), 6,7,15,28,32,34,35,38 followed by Japan (n=4 [21.1%]), 16,36,37,40 China (n=3 [15.8%]), 29,33,39 Korea (n=1 [5.3%]), 21 Israel (n=1 [5.3%]), 30 Canada (n=1 [5.3%]), 31 and Australia (n=1 [5.3%]). 41 All 19 studies examined the effect of endometriosis on the incidence of placenta previa (Table 1).…”
Section: Studymentioning
confidence: 99%